Leading priorities for development of the high technologies market - Chlivickas, Eugenijus; Petrauskaitė, Neringa; Ambrusevič, Nikolaj (Journal of Business Economics and Management, 2009)
High technologies development has strategic importance to improving regional EU and national economies effectiveness and assuring a country's competitiveness. This is especially a key priority for small countries that do not have many natural and material resources, as well as labour force. Therefore, in the article the specifics of high technologies development that derives from exceptional high technologies features is analysed. These specific features of high technologies influence the rise of specific characteristics of high technologies market. Thus, the article aims to set leading priorities for a successful development of high technologies business in Lithuania. Development of the high technologies business depends first of all on development of the high technologies market. The success of developing high technologies depends on implementation of the ‘ triple helix’ model covering integration of the public and private sector as well as science. The most successful’ triple helix’ model for high technologies development is the one where the highest degree of cooperation between authorities, industry and academic public is indicated. Therefore the article establishes the implementation of the ‘ triple helix’ as a leading priority for high technologies development in Lithuania.First Publish Online: 14 Oct 2010